2008
DOI: 10.1128/jb.00089-08
|View full text |Cite
|
Sign up to set email alerts
|

Integration Host Factor Positively Regulates Virulence Gene Expression in Vibrio cholerae

Abstract: Virulence gene expression in Vibrio cholerae is dependent upon a complex transcriptional cascade that is influenced by both specific and global regulators in response to environmental stimuli. Here, we report that the global regulator integration host factor (IHF) positively affects virulence gene expression in V. cholerae. Inactivation of ihfA and ihfB, the genes encoding the IHF subunits, decreased the expression levels of the two main virulence factors tcpA and ctx and prevented toxin-coregulated pilus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 71 publications
1
70
0
Order By: Relevance
“…It has also been shown that IHF activates Pe transcription indirectly via the alleviation of H-NS-mediated repression (van Ulsen et al, 1996). Recent reports further reinforce the role of IHF in alleviating H-NS silencing in Vibrio cholerae (Stonehouse et al, 2008) and in the csgD operon of E. coli (Ogasawara et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…It has also been shown that IHF activates Pe transcription indirectly via the alleviation of H-NS-mediated repression (van Ulsen et al, 1996). Recent reports further reinforce the role of IHF in alleviating H-NS silencing in Vibrio cholerae (Stonehouse et al, 2008) and in the csgD operon of E. coli (Ogasawara et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…The existence of toxR gene is significant as a regulating agent for expression and function of several other genes, which are on turn responsible for the pathogenecity of V. cholerae (9,26,27). Furthermore, toxR gene does not horizontally get transferred from pathogenic strains to non-pathogenic ones (28); hence, it is specific to vibrionacea.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to IHF, H-NS also affects DNA architecture, and it is known to repress gene expression under conditions of low temperature or low osmolarity (189). While the conditions that control MvaT/MvaU activity are unknown, IHF antagonizes H-NS-dependent silencing of gene expression in bacterial pathogens, including E. coli, V. cholerae, and S. enterica (190)(191)(192). Further studies are needed to determine whether IHF antagonizes MvaT/MvaU-dependent repression of RsmZ.…”
Section: P Aeruginosamentioning
confidence: 99%